Propagules of Rhizophora mangle (Rhizophoraceae) bored by Coccotrypes rhizophorae (Coleoptera: Curculionidae) in the Tumilco mangrove, Veracruz, México. - Martínez-Zacarías, Alejandro Arturo; Chamorro-Florescano, Ivette Alicia; Pech-Canché, Juan Manuel; Alanís Méndez, José Luis; Basáñez-Muñoz, Agustín de Jesús (Revista de Biología Tropical, 2017)
Mangrove species propagules represent a particular survival and dispersal strategy. Unfortunately, some reports have stated that Rhizophora mangle propagules are frequently attacked by Coleoptera and Lepidoptera before and after their dispersion period. The beetle species Coccotrypes rhizophorae is an obligate parasite that can cause mortality in propagules and seedlings of R. mangle, and may modify the structure of its populations. Because of the importance on this mangrove species, survival and increasing human impacts in the area, this study evaluated the presence of propagules with C. rhizophorae boring evidence in the Tumilco mangrove, in Veracruz State, Mexico. For this, three sampling areas were established: 1) mangrove core of R. mangle, 2) most impacted edge of an unpaved road with R. mangle and A. germinans, and 3) edge with Typha latifolia and R. mangle; in each area, three 25x25 m random plots were analyzed. The number of bored propagules per site was recorded every 15 days over a sampling period of one year (n= 567) from January to December 2012. We also observed the damaged part of the propagule (basal, central, apical) and the number of live and dead bored propagules per season, and compared results for different seasons in the area: rainy, cold northerly fronts or “norte” and dry. Insects were identified by an expert. Our results showed that a higher number of bored propagules was observed during the dry season, mainly in zones 2 and 3. Survival of bored propagules was higher when the perforation occurred in the basal part of the plant, and during the dry and norte seasons. Study zone 2 in particular presented a higher number of live propagules when the damage occurred in the basal part of the propagule. In all three zones, mortality was higher when the damage was apical. Zones 1 and 3 presented higher propagule survival during the dry season, while survival in zone 2 was higher during the rainy and norte seasons. The number of propagules decreased with rising flooding levels. The results showed that C. rhizophorae has a wide distribution in the Tumilco mangrove, but the mortality of R. mangle propagules is influenced by the part of the propagule that suffers damage, as well as by the season of the year and the characteristics of the area in which the infestation occurs. Futher studies are required to evaluate the impact of propagule mortality on the population structure of R. mangle.